2021
DOI: 10.1097/tp.0000000000003879
|View full text |Cite
|
Sign up to set email alerts
|

The Abundance of Antigalactose-deficient IgA1 Autoantibodies Results in Glomerular Deposition and IgA Nephropathy Recurrence After Renal Transplantation

Abstract: The clinical trial registration number is UMIN000023787.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…Importantly, atacicept treatment led to dose-dependent reductions in serum Gd-IgA1, and the reduced Gd-IgA1 level was significantly correlated with improvements in proteinuria ( 67 ). Additionally, some studies have shown that the recurrence of IgAN in allograft kidneys is associated with high serum Gd-IgA1 levels ( 68 70 ). Moreover, serum Gd-IgA1 level may be a potential biomarker for the diagnosis and activity assessment of recurrent IgAN after kidney transplantation ( 71 73 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, atacicept treatment led to dose-dependent reductions in serum Gd-IgA1, and the reduced Gd-IgA1 level was significantly correlated with improvements in proteinuria ( 67 ). Additionally, some studies have shown that the recurrence of IgAN in allograft kidneys is associated with high serum Gd-IgA1 levels ( 68 70 ). Moreover, serum Gd-IgA1 level may be a potential biomarker for the diagnosis and activity assessment of recurrent IgAN after kidney transplantation ( 71 73 ).…”
Section: Discussionmentioning
confidence: 99%
“…Atacicept, a blocker of BLyS and APRIL, has the potential to improve proteinuria and renal function and has an acceptable safety profile in patients with IgAN. Importantly, atacicept treatment led to dose-dependent reductions in serum Gd-IgA1, and the reduced Gd-IgA1 level was significantly correlated with improvements in proteinuria (67). Additionally, some studies have shown that the recurrence of IgAN in allograft kidneys is associated with high serum Gd-IgA1 levels (68-70).…”
Section: Findings In the Context Of Other Literaturementioning
confidence: 98%
“…Evaluation of these assessments should be made in future prospective cohorts. Finally, although an association between anti-Gd-IgA1-specific autoantibodies and IgA deposition in the allograft has been reported [ 28 ], anti-Gd-IgA1-specific autoantibodies were not investigated in this study. However, other researchers found that serum anti-Gd-IgA1-specific autoantibodies did not predict outcome in the native kidney [ 36 ].…”
Section: Discussionmentioning
confidence: 98%
“…KM55 staining has also been found to be positive in allograft kidneys with IgAN [ 24 , 25 ]. It has also been reported that serum and urinary Gd-IgA1 quantification is useful for evaluation of the activity of IgAN in the native kidney [ 18 , 26 , 27 ], and the recurrence of IgAN in allograft kidneys is associated with a high Gd-IgA1 levels [ 28 30 ]. However, until now, there has been no system for classification of IgA deposition in allografts that includes both serological and histopathological assessment of Gd-IgA1.…”
Section: Introductionmentioning
confidence: 99%
“…In this report, the IgAN recurrence group demonstrated significantly higher serum αIgA levels at the time of recurrence confirmation. The IgAN recurrence group also exhibited higher intragraft αIgA and relatively higher ICs than those of a non-IgAN recurrence group [62]. According to these reports, therefore, it is reasonable to believe that GdIgA1 and αIgA are key molecules in IgAN recurrence and important targets to prevent recurrence.…”
Section: Iga Nephropathymentioning
confidence: 92%